Repurposing Riociguat for Treatment of Refractory Angina Resulting From Coronary Spasm - Valeria Martínez Pereyra, MS; Andreas Seitz, MD; Astrid Hubert, PhD; Sascha Beck, MS; Ute Hofmann, PhD; Matthias Schwab, MD; Raffi Bekeredjian, MD; Udo Sechtem, MD; Peter Ong, MD (JACC: Case Reports, 2021)
Coronary spasm is a frequent cause of angina despite unobstructed coronary arteries, and symptom control with recommended drugs is limited. We report the case of a 77-year-old woman who had refractory angina despite conventional antianginal treatment. Repurposing riociguat, a soluble guanylate cyclase stimulator, resulted in improvement of symptoms and prevention of spasm. (Level of Difficulty: Intermediate.)